Pemberdayaan UMKM Desa Tegalpapak Melalui Program Pembuatan NIB dan Sertifikat Halal untuk Legalitas Usaha (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze in depth the influence of business legality on the growth and increased competitiveness of Micro, Small, and Medium Enterprises (MSMEs). Business legality is seen as a crucial foundation in strengthening the position of MSMEs in the market, as it not only provides legal certainty but also fosters consumer trust in the quality of the products offered. This study uses a qualitative approach with data collection techniques such as field observations, in-depth interviews with business actors, and relevant documentation studies. The results show an increase in public awareness of the importance of having business legality, as evidenced by the increasing number of MSMEs officially registering their business permits. Furthermore, legality has been proven to increase the credibility of MSMEs, expand market access, facilitate collaboration with the private sector and government agencies, and open up opportunities for obtaining capital support. A significant increase in consumer trust is also evident, as MSME products with legality are more easily accepted and marketed through various distribution channels. Thus, this study confirms that business legality is not merely an administrative requirement, but rather a strategy that can encourage sustainable business growth and increase competitiveness at the local and national levels. In conclusion, the synergy between MSMEs and the government is the main key in encouraging the creation of a healthy, transparent, and highly competitive business ecosystem.